2018
DOI: 10.1186/s12909-018-1335-7
|View full text |Cite
|
Sign up to set email alerts
|

Influences on students’ empathy in medical education: an exploratory interview study with medical students in their third and last year

Abstract: BackgroundEmpathy is beneficial for patients and physicians. It facilitates treatment and improves physical and psychosocial outcomes. The therapeutic relevance of empathy emphasizes the need to help medical students develop their empathic abilities. Our study aimed to identify factors which promote or hinder the development and expression of empathy in medical students during the course of their studies.MethodsWe interviewed 24 medical students (six male and six female students in their 6th semester as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 62 publications
3
84
0
5
Order By: Relevance
“…Insecurity or a lack of routine has previously been shown to decrease students´ empathy. 19 This factor can be counteracted by an increase in medical knowledge and clinical skills, whereas the other inhibitor, a stressful and empathy-hostile medical culture, is more difficult to change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insecurity or a lack of routine has previously been shown to decrease students´ empathy. 19 This factor can be counteracted by an increase in medical knowledge and clinical skills, whereas the other inhibitor, a stressful and empathy-hostile medical culture, is more difficult to change.…”
Section: Discussionmentioning
confidence: 99%
“…In a German study based on interviews with 24 medical students either during their sixth term or during their final clinical year, empathic behaviour appeared to be influenced not only by the surrounding medical culture but also by aspects of the courses and by individual students and patient characteristics. 19 However, the researchers did not investigate whether the empathy of the interviewed students changed during their medical education.…”
Section: Introductionmentioning
confidence: 99%
“…According to scientific views from the Medicine field, empathy can be learned and Medical schools should educate their students in this respect [63,64]. Many studies have pointed out the necessity for future professionals to receive training in order to enhance their empathetic skills [64,65].…”
Section: Factors That Influence Empathymentioning
confidence: 99%
“…17,30 The present study demonstrated that Croatian students ob- Numerous studies have reported an increase in empathy with training and progression in communication skills. [33][34][35][36][37][38] Previous research studies revealed that exercises in verbal and non-verbal communication as well as early encounters with patients significantly improved empathy level in medical professionals and students. A comparison of the curriculum between the two dental TA B L E 5 The difference in levels of total empathy and its components between Polish and Croatian students in relation to the year of training increase in empathy level.…”
Section: Ta B L Ementioning
confidence: 99%